2004
DOI: 10.5558/tfc80251-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fire severity and salvage logging traffic on regeneration and early growth of aspen suckers in north-central Alberta

Abstract: The Forestry Chronicle Downloaded from pubs.cif-ifc.org by 34.218.44.141 on 05/11/18For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…In the present analysis, it is clear that ramet density and growth rates were greater with increased fire severity, as has been shown in Arizona (Bailey and Whitham 2002), Alberta (Fraser et al 2004), and South Dakota (Keyser et al 2005). There are two important caveats to this trend: (1) the presence of heavy coarse woody debris within an aspen stand and (2) heavy post-fire ungulate browsing pressure.…”
Section: Management Wildfire and Aspen Regenerationsupporting
confidence: 57%
See 1 more Smart Citation
“…In the present analysis, it is clear that ramet density and growth rates were greater with increased fire severity, as has been shown in Arizona (Bailey and Whitham 2002), Alberta (Fraser et al 2004), and South Dakota (Keyser et al 2005). There are two important caveats to this trend: (1) the presence of heavy coarse woody debris within an aspen stand and (2) heavy post-fire ungulate browsing pressure.…”
Section: Management Wildfire and Aspen Regenerationsupporting
confidence: 57%
“…Many have advocated for the importance of severe disturbances for adequate aspen regeneration (DeByle and Winokur 1985), yet empirical studies are split on the question of fire severity on aspen regeneration, and there is no clear consensus among their findings. Bailey and Whitham (2002), Keyser et al (2005), Fraser et al (2004), and Wan et al (2014) found that fire severity was positively associated with post fire aspen sprout density. Horton and Hopkins (1965) and Wang (2003) found a negative relationship, and Brown and DeByle (1987) and Bartos et al (1994) found no clear relationship between fire severity and post fire aspen regeneration and growth.…”
Section: Burn Severitymentioning
confidence: 99%
“…Generally, then, in most cases where there has been an intense fire on an upland site with at least some component of pine species or black spruce, natural regeneration density exceeds forestry stocking standards (Donato et al 2006). As for aspen, contradictory results have been reported in the literature on the effect of fire severity, as Fraser et al (2004) observed little or no effect of severity on density of suckers, while Wang (2003) and Greene et al (2004) reported significantly lower density of suckers on severely burned plots. Nonetheless, the variation in stocking for asexual aspen along a canopy severity gradient is slight compared to the seedbed-mediated response of sexual stems.…”
Section: Tree Regenerationmentioning
confidence: 49%
“…As for the response of sprouting species, Fraser et al (2004) reported a 60% decrease in aspen sucker densities due to physical damage with a winter harvest immediately after a summer fire. Likewise, Kurulok and MacDonald (2004) observed a 50% decline in deciduous (mainly aspen) recruit density due to salvage.…”
Section: Tree Regenerationmentioning
confidence: 99%
“…On the other hand, given sufficient fire residence time, heat penetration into soil can be damaging to aspen root stocks (Brown and DeByle, 1987;Perala, 1991). Other studies have found that fire severity can enhance subsequent dominance by aspen (Frelich and Reich 1995;Fraser et al, 2004). In the case of the PCF, we hypothesized that higher fire severity areas would positively affect aspen abundance and negatively affect species richness (Turner et al, 1997;Wang and Kemball, 2005).…”
Section: Introductionmentioning
confidence: 99%